Use of digitized images to evaluate the quality of coffee seeds - Rocha, Ygor Lázaro Burjack Ribeiro; Costa, Rômulo Rayan; Araújo, Nicolas Oliveira de; Freire, Ana Izabella; Souza, Filipe Bittencourt Machado de; Cruz, Renata Ranielly Pedroza; Melo, Carlos Cicinato Vieira (Seven Editora, 2024)
The analysis of digital images consists of the generation of dimensional data, such as width, length and area, or attributes, such as color and texture of a captured image, and their measurement by means of counting or frequency methods. The use of image analysis to evaluate the physiological quality of seeds has been considered an objective, economical and practical method. Thus, this work was carried out with the objective of comparing the results of the evaluation of the physiological quality of coffee seeds obtained in the germination tests with those obtained from the analysis of digitized images. Thirty-two lots of coffee seeds were used, which were submitted to conventional analysis and image analysis using the computer program WINFOLIA.® Although additional research is needed to confirm the results, it has been observed that the image analysis method can accurately provide the germination and vigor of coffee seeds in a more practical, economical and anticipated way than the conventional test. DOI:https://doi.org/10.56238/sevened2023.001-023